Adipose Fatty Acid Binding Protein Promotes Saturated Fatty Acid-induced Macrophage Cell Death through Enhancing Ceramide Production - Zhang, Yuwen (J Immunol, 2016)
Macrophages play a critical role in obesity-associated chronic inflammation and disorders. However, the molecular mechanisms underlying the response of macrophages to elevated fatty acids (FAs) and their contribution to metabolic inflammation in obesity remain to be fully elucidated. Here, we report a new mechanism by which dietary FAs, in particular saturated FAs, are able to directly trigger macrophage cell death. We demonstrated that excess saturated FAs, but not unsaturated FAs, induced the production of cytotoxic ceramides in macrophage cell lines. Most importantly, expression of adipose fatty acid binding protein (A-FABP) in macrophages facilitated metabolism of excess saturated FAs for ceramide synthesis. Inhibition or deficiency of A-FABP in macrophage cell lines decreased saturated FA-induced ceramide production, thereby resulting in reduced cell death. Furthermore, we validated the role of A-FABP in promoting saturated FA-induced macrophage cell death with primary bone-marrow derived macrophages and high-fat diet-induced obese mice. Altogether, our data reveal that excess dietary saturated FAs may serve as direct triggers in induction of ceramide production and macrophage cell death through elevated expression of A-FABP, thus establishing A-FABP as a new molecular sensor in triggering macrophage-associated sterile inflammation in obesity.